2019
DOI: 10.1002/cctc.201900454
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen‐Vacancy‐Mediated Photocatalysis over Bi2Sn2O7: Exceptional Catalytic Activity and Selectivity

Abstract: A series of Bi2Sn2O7 photocatalysts was developed with the aim to regulate defect chemistry as well as electronic structure by modulating the charge states of tin species for boosting photocatalytic selective oxidation of alcohols performance. Defective centers, such as oxygen vacancies (OVs), were beneficial to enhancing the adsorption and activation of molecular oxygen. Meanwhile, the valence band edge potential of Bi2Sn2O7 with higher OVs content exhibited a distinct downshift, improving the thermodynamical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…According to previous reports, surface defect centers play an important role in determining the photocatalytic degradation performance for organic dye wastewater, and could serve as electron trap centers to improve photogenerated charge carrier separation. 19 As shown in Fig. 4b, the higher EPR intensity of BiOBr 0.25 Cl 0.75 indicated that abundant defect centers were produced during solid solution formation, which contributed to boosting the photocatalytic properties.…”
mentioning
confidence: 84%
“…According to previous reports, surface defect centers play an important role in determining the photocatalytic degradation performance for organic dye wastewater, and could serve as electron trap centers to improve photogenerated charge carrier separation. 19 As shown in Fig. 4b, the higher EPR intensity of BiOBr 0.25 Cl 0.75 indicated that abundant defect centers were produced during solid solution formation, which contributed to boosting the photocatalytic properties.…”
mentioning
confidence: 84%
“…In order to improve the photocatalytic oxidation of alcohols, Huang et al . developed a series of Bi 2 Sn 2 O 7 photocatalysts by modulating the charge states of tin species . Oxygen vacancies as a defective center help encourage the adsorption and activation of molecular oxygen.…”
Section: Figurementioning
confidence: 99%
“…Among the photocatalysts studied, SrTiO 3 has been attracting much interest as the active photocatalyst and this oxide has wide band gap (3.2 eV) and high chemical stability with perovskite structure . High apparent quantum yield (>60 %) at 380 nm light is reported for Al and Mo modified SrTiO 3 . However, because of large band gap, SrTiO 3 based catalyst can be only driven by UV light that is to go beyond goal for high efficiency for converting solar to hydrogen.…”
Section: Introductionmentioning
confidence: 99%
“…Utilization of oxygen vacancy has focused as facile and efficient way in order to increase photocatalytic activity, because it is considered that oxygen vacancy could work for charge separation and also forms absorption band in visible light region . Those properties can role to transfer a charge that suppress recombination of electron and hole (backward reaction) in photocatalytic reaction . However, excess amount of oxygen vacancies also works as recombination site .…”
Section: Introductionmentioning
confidence: 99%